Pengembangan Media Komik Berbasis Smartphone untuk Meningkatkan Hasil Belajar dan Minat Baca Peserta Didik dengan Muatan Pelajaran IPS Kelas 4 - Yahya Wibisono Putro; Firosalia Kristin (Departement of Mathematics Education, 2023)
The purpose of this research is to develop smartphone-based comic media to improve learning outcomes and interest in reading in fourth grade elementary school students. The type of research used is research and development (R&D). The subjects of this study were fourth grade students at SD Negeri 2 Sukodono with a total of 30 students, 13 male students and 17 female students. Data collection techniques are interviews, questionnaires and tests. The instruments used were interview sheets, expert validator sheets and multiple choice questions. Based on the results of the validation experts from 4 media expert validators, the material expert got a score of 42 out of a score of 84% in the very high category, the media expert got the percentage of 92% in the very high category, the results of the design expert got the percentage of 84% in the very high category, and the results of language experts get a percentage of 94% in the very high category. The results of the effectiveness of the t test Sig. (2-tailed) .000 < 0.05 Ho is rejected and there is a difference in the increase in learning outcomes, it can be stated that the developed smartphone-based comic media has been effective in improving student learning outcomes. While the results of the questionnaire obtained a percentage of 97.5 with a very high category. From the results of research conducted by smartphone-based comic media, it can improve learning outcomes and interest in reading in class IV students.